THE ADVANTAGES AND DISADVANTAGES OF USING ICT IN ENGLISH LANGUAGE TEACHING - Paramitasari, Ayu (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2020)
Abstract: Information-communication technologies (ICT) are a part ofour world and we use it everyday. ICTs are used in many aspect of life,such as: economic, healthy, social, and education. Teaching techniqueusing chalk and talk or explanation is not popular anymore. It is thensuggested that the teacher uses internet within his teaching learningprocess and it is also compulsory for the students to learn to use it. TheInternet is a must, because it can be used (1) as the source of knowledge(2) as an aid for learning (instructional aid) (3) as teaching or learningfacility (4) as a standard of competency (5) as an administrativeequipment (6) as a supporting equipment for the school management (7)as an educational infrastructure. In language teaching and learning, wehave alot of ways to choose from the world of technology: Radio, TV,CD Rom, Computers, C.A.L.L., The Internet, Electronic Dictionary,Email, Blogs and Audio Cassettes, Power Point, Videos, DVD’s orVCD’s. ICT can also be very attractive for students. The effectivenessof ICT in education is demonstrated by the achievement ofcommunication objectives, while efficiency is showed by saving cost,time and effort. In use in the educational process, theoretically, ICTwould bring positive benefits. For all education participants, bothteachers and students, ICT helps to provide a huge and variousknowledge as well as up to date and easily accessible in a relativelyrapid and in some cases even is free of charge. As a result technologyplays a ver important role in English teaching. Using multimedia tocreate a context or task to teach English has an advantages. This articletry to presents pluses and minuses of ICT usage in English LanguageTeaching (ELT).Key words: Infomation-communication technology (ICT), ICTs tools,pluses and minuses of ICT, multimedia in English teaching, teachinglearning process.